1984
DOI: 10.1085/jgp.83.6.801
|View full text |Cite
|
Sign up to set email alerts
|

Cl-/HCO3- exchange at the apical membrane of Necturus gallbladder.

Abstract: AB S T R A C T The hypothesis of Cl -/HCO s exchange across the apical membrane of the epithelial cells of Necturus gallbladder was tested by means of measurements of extracellular pH (pH.), intracellular pH (pHi), and Cl -activity (aCli) with ion-sensitive microelectrodes. Luminal pH changes were measured after stopping mucosal superfusion with a solution of low buffering power. Under control conditions, the luminal solution acidifies when superfusion is stopped. Shortly after addition of the Na'/H' exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 35 publications
4
44
0
Order By: Relevance
“…From the initial rate of change of the extracellular pH and the buffering power ofthe solution, an apparent H+ flux (OH) was computed and normalized to that determined under control conditions (NaCl HEPES-Ringer's, before theophylline) . In the absence of theophylline, both amiloride and Na'-free medium reversed the luminal acidification to luminal alkalinization, as previously reported (Reuss and Costantin, 1984). The larger alkalinization observed in Na*-free medium compared with amiloride is due to reversal of the Na''/H+ exchange in the former condition .…”
Section: Extracellular Ph Measurementssupporting
confidence: 85%
See 4 more Smart Citations
“…From the initial rate of change of the extracellular pH and the buffering power ofthe solution, an apparent H+ flux (OH) was computed and normalized to that determined under control conditions (NaCl HEPES-Ringer's, before theophylline) . In the absence of theophylline, both amiloride and Na'-free medium reversed the luminal acidification to luminal alkalinization, as previously reported (Reuss and Costantin, 1984). The larger alkalinization observed in Na*-free medium compared with amiloride is due to reversal of the Na''/H+ exchange in the former condition .…”
Section: Extracellular Ph Measurementssupporting
confidence: 85%
“…In parallel with these studies, we demonstrated the existence of an Na'/H' exchanger at the apical membrane of Necturus gallbladder epithelium, whose rate under control conditions accounts for at least 75% of Na' entry Reuss, 1982, 1984;Reuss, 1984). This cation exchanger operates in parallel with a Cl-/ HC03 exchanger (Reuss and Costantin, 1984), which in turn accounts for the rate of transepithelial Cl-transport (Reuss, 1984).…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations